Nutritional Status of Young Athletes in Central Java, Indonesia - Mardiana, Mardiana; Kartini, Apoina; Sutiningsih, Dwi; Suroto, Suroto (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2024)
Proper nourishment is vital for persons who participate in physical activity and require increased amounts of important nutrients. Adolescents should give priority to this matter, as their developing bodies require greater nutritional requirements to support their growth and physical activity. An investigation carried out on adolescent athletes in Indonesia revealed that sports schools and athlete training facilities frequently encounter insufficient food consumption, which may have an impact on athlete performance and long-term well-being. The study aimed to examine the nutritional factors that influence body fat in young athletes who are enrolled in sports schools in Central Java, Indonesia. The study was conducted with the participation of 110 young athletes. The data for this study were analyzed using Pearson correlation and multiple linear regression. The result shows a relationship between gender, energy intake, protein intake, physical activity, and body fat percentage, as well as a correlation between age and BMI for age. The result of the multivariate analysis suggests that gender had the most effect on body fat percentage (r=0.77; p-value=0.0001). Young athletes should receive comprehensive education and monitoring from certified experts to ensure eating and exercise habits that enhance performance and promote long-term health.